JOOL: A TECHNOLOGY INTERVENTION TO IMPROVE PURPOSE IN LIFE: FOCUS GROUP ANALYSIS. (11th November 2018) - Kraemer, S; Tkatch, R; Albright, L; Martin, D; Wicker, E
Abstract: Having a sense of purpose encompasses meaning in life, goals, directions and is associated with positive health outcomes important to successful aging. The purpose of this study is to understand the effectiveness of a purpose in life intervention administered via smartphone phone app and how to best adapt this application for older adults. Two focus groups were conducted (n=7, n=7) 1) to better understand how older adults define purpose in life, 2) how they currently use technology for their health, and 3) how they would potentially use technology to help improve purpose in life. Themes identified included the importance of staying independent, faith, health concerns, and social connectedness. Participants expressed significant interest in the use of the application. The next phase of this intervention will test the use of the application with older adults. Pre/post surveys will be used to measure purpose in life, resilience, optimism, and quality of life.